The influence of chop location on pork loin quality - Homm, J.W.; Johnson, R.C.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Pork longissimus muscle quality characteristics were evaluated on 109 center cut boneless loins. After 21 d aging, loins were cut into 1-inch chops and allowed to bloom for 30 minutes before visual measurements (color, marbling and firmness) and instrumental color were recorded for each chop. Overall, visual color was the lightest on the anterior and posterior ends and was the darkest from approximately 50% to 80% of the length of the loin. Marbling was the highest at the posterior end, lowest in mid-loin, then higher toward the anterior end. Loins were the softest at the anterior end and became firmer toward the posterior end. From the anterior to approximately 40- 50% of the loin length, chops became darker (lower L*), redder (higher a*), and less yellow (lower b*). Near the center of the loin, color was constant, but became lighter (higher L*) and more yellow (higher b*) at the posterior end. Chops located at 25% (anterior), 50% (middle) and 75% (posterior) of the length of each loin were collected and further analyzed. Section chops within loins had similar pH values. The chop from the anterior section contained the highest percentage of crude fat, followed by the posterior section chop, and the middle section chop contained the lowest percentage. The middle section chop contained the highest percentage of moisture. The posterior section chop had more moisture display loss than the anterior and middle section chops. The anterior section chop had more cooking loss than the posterior section chop. Chops became progressively less tender the more posterior the section location.
Keywords: Chop location; Pork quality; Longissimus; Swine